An environmentally-friendly explosion-proof marble powder coating with stone touch simulation and a preparation method thereof
Patent Information
- Application Number
- CN202610044028.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-01-14
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2046-01-14
AI Technical Summary
然而,现有仿石粉末涂料在表面质感控制、防爆性能及可喷涂性方面仍存在诸多问题
在表面结构调控方面,本发明引入微米级硬相无机填料与亚微米级软相无机填料的协同复配机制,利用其在粒径级配、堆积致密性及流平行为中的互补作用,实现对涂膜表面粗糙度(Ra 3~8 μm)与摩擦系数(0.65~0.85)的精准控制,从而获得与天然石材高度相似的细腻触感与阻尼感。同时,该填料复配体系具有良好的可分散性与级配稳定性,显著提升了粉末涂料的批次一致性与装饰稳定性。
Smart Images

Figure CN122080746B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of powder coating technology, specifically relating to an environmentally friendly explosion-proof powder coating for simulating the texture of stone marble and its preparation method. Background Technology
[0002] Powder coatings, as a green and environmentally friendly coating material, are widely used in architectural decoration, industrial manufacturing, and home furnishing due to their solvent-free nature, low construction waste, and high film-forming efficiency. In recent years, with the increasing demand from consumers for both highly realistic decorative effects and safe construction performance, imitation stone powder coatings, which possess the appearance and feel of natural stone, have gradually gained attention. However, existing imitation stone powder coatings still have many problems in terms of surface texture control, explosion-proof performance, and sprayability. On the one hand, traditional imitation stone coatings often rely on the accumulation of large-particle colored sand or coarse fillers to create a tactile feel, but their surface roughness is difficult to control precisely, easily resulting in uneven particle texture and large differences between batches, making it difficult to achieve the delicate touch and consistency of real stone. On the other hand, to improve the coating texture and hiding power, fine-particle inorganic components are often required, but the finer the powder particle size, the stronger its aggregation and electrostatic sensitivity during electrostatic spraying, which can easily cause dust explosion risks and increase industrial safety hazards.
[0003] Furthermore, existing explosion-proof powder coatings mostly use dark-colored carbon-based conductive fillers, such as carbon black or graphite. Although these can create charge discharge paths, they severely affect the stone-like decorative effect, especially the visual quality of light-colored or light-colored coatings. Therefore, how to achieve safe spraying without affecting the simulation effect, and how to construct a powder coating system with controllable tactile feedback, explosion-proof capability, and environmentally friendly properties, has become a pressing technical challenge in this field. Summary of the Invention
[0004] To address the shortcomings mentioned in the background art, the present invention aims to provide an environmentally friendly explosion-proof powder coating for simulating the feel of stone marble and its preparation method. By using multi-level filler particle size distribution and flow parallelism in the powder coating to synergistically control the coating roughness, and by introducing a light-colored semi-conductive inorganic phase to construct a charge discharge channel, the excellent stone-like feel and explosion-proof performance are synergistically improved.
[0005] The objective of this invention can be achieved through the following technical solutions: An environmentally friendly explosion-proof powder coating for simulating the feel of marble, comprising the following raw materials in parts by weight: 40-60 parts resin matrix, 15-25 parts micron-sized hard phase inorganic filler, 3-8 parts submicron-sized soft phase inorganic filler, 3-6 parts light-colored semi-conductive inorganic phase, 2-5 parts environmentally friendly color paste, 0.5-1.2 parts aminosilane coupling agent, 0.5-0.8 parts titanate coupling agent, 1.0-1.5 parts low-migration acrylic leveling agent, 0.3-0.5 parts polyethylene wax powder, and 2-4 parts curing agent; The mass ratio of the micron-scale hard phase inorganic packing to the submicron-scale soft phase inorganic packing is 4:1 to 6:1.
[0006] More preferably, the resin matrix is an environmentally friendly polyester resin; the micron-sized hard phase inorganic filler is selected from one or more of quartz powder, talc powder, silica powder, and calcium aluminate; the submicron-sized soft phase inorganic filler is selected from one or more of modified calcium carbonate with surface stearic acid coating, submicron-sized talc powder, submicron-sized kaolin, and submicron-sized wollastonite.
[0007] More preferably, the light-colored semiconductive inorganic phase is antimony-doped tin dioxide with a whiteness of not less than 85%; the environmentally friendly color paste is a composite color paste of heavy metal-free titanium dioxide and carbon black; and the curing agent is triglycidyl isocyanurate.
[0008] More preferably, the median particle size D50 of the volume distribution of the light-colored semiconducting inorganic phase is 1.0 to 3.0 μm, and the critical percolation threshold of the light-colored semiconducting inorganic phase in the powder coating system is 4.2%.
[0009] More preferably, the median particle size D50 of the micron-sized hard phase inorganic filler is 8–25 μm, the particle size distribution range is D10 ≥ 3 μm, D90 ≤ 40 μm, and the particle size distribution index n is 0.3–0.5; The submicron-sized soft-phase inorganic filler has a median particle size D50 of 0.2–1.0 μm, a particle size distribution range of D10 ≥ 0.1 μm and D90 ≤ 2 μm, and a particle size distribution index n of 0.6–0.8. The particle size distribution width (Span) of the composite packing system composed of micron-sized hard-phase inorganic packing and submicron-sized soft-phase inorganic packing is not greater than 2.5.
[0010] A method for preparing an environmentally friendly explosion-proof powder coating that simulates the feel of natural marble includes the following steps: S1. Synthesize a light-colored, semi-conductive inorganic phase; S2. The resin matrix, micron-sized hard phase inorganic filler, submicron-sized soft phase inorganic filler, light-colored semi-conductive inorganic phase, environmentally friendly color paste, aminosilane coupling agent, titanate coupling agent, low-migration acrylic leveling agent, polyethylene wax powder and curing agent are premixed to obtain a premix; S3. The premixed material is melt-extruded, cooled, and pressed into sheets to obtain sheet material; S4. The sheet material is crushed and graded to obtain the stone-touch simulated marble environmentally friendly explosion-proof powder coating.
[0011] More preferably, the synthesis method of the light-colored semiconducting inorganic phase in step S1 is the sol-gel method, which includes the following steps: S101. Dissolve tin tetrachloride pentahydrate and antimony trichloride in anhydrous ethanol, add citric acid, adjust the pH of the system to 3-4, and react under stirring to form a sol. S102. The sol is dried to obtain a dry gel; S103. The dry gel is calcined and pulverized to obtain a light-colored semi-conductive inorganic phase.
[0012] More preferably, in step S101, the molar ratio of tin tetrachloride pentahydrate to antimony trichloride is 100:5 to 100:10; the molar ratio of citric acid to the total amount of metal ions is 1.2:1; the stirring reaction temperature is 60 to 70°C; and the reaction time is 2 to 3 hours.
[0013] More preferably, the premixing in step S2 is carried out using a high-speed mixer with a mixing speed of 800-1000 r / min and a mixing time of 5-8 min; the melt extrusion in step S3 is carried out using a twin-screw extruder with a low-temperature segmented extrusion temperature zone, a screw shear strength of no more than 0.8 MPa, and a screw speed of 300-400 r / min.
[0014] More preferably, the surface roughness Ra of the coating film formed after the powder coating is cured is 3 to 8 μm, and the surface friction coefficient is 0.65 to 0.85.
[0015] The beneficial effects of this invention are: In terms of surface structure control, this invention introduces a synergistic compounding mechanism of micron-sized hard-phase inorganic fillers and submicron-sized soft-phase inorganic fillers. Utilizing their complementary effects in particle size distribution, packing density, and flow parallelism, precise control of the coating surface roughness (Ra 3–8 μm) and coefficient of friction (0.65–0.85) is achieved, resulting in a delicate tactile feel and damping sensation highly similar to natural stone. Simultaneously, this filler compounding system exhibits excellent dispersibility and gradation stability, significantly improving the batch consistency and decorative stability of powder coatings.
[0016] Regarding the improvement of explosion-proof performance, this invention introduces a light-colored semi-conductive inorganic phase into the powder system at a critical percolation concentration (4.2%) to construct microscale charge discharge channels. This significantly improves the minimum ignition energy and surface resistance control capability of the coating, effectively suppressing the risk of dust explosion caused by electrostatic accumulation during spraying, while maintaining the light-colored appearance of the powder and avoiding the damage to the stone-like decorative effect caused by traditional carbon black conductive fillers. Furthermore, this system, combined with environmentally friendly polyester resin and low-migration additives, ensures coating safety while also meeting the requirements for low VOC emissions and green construction. Attached Figure Description
[0017] The invention will now be further described with reference to the accompanying drawings.
[0018] Figure 1 This is a graph showing the relationship between Ra and friction coefficient in the embodiments and comparative examples of the present invention. Detailed Implementation
[0019] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0020] Example 1: The stone-touch simulated marble environmentally friendly explosion-proof powder coating comprises the following raw materials in parts by weight: 40 parts resin matrix, 15 parts micron-sized hard phase inorganic filler, 3 parts submicron-sized soft phase inorganic filler, 3 parts light-colored semi-conductive inorganic phase, 2 parts environmentally friendly color paste, 0.5 parts aminosilane coupling agent, 0.5 parts titanate coupling agent, 1.0 part low-migration acrylic leveling agent, 0.3 parts polyethylene wax powder, and 2 parts curing agent; The preparation steps of the environmentally friendly explosion-proof powder coating for simulating the texture of stone marble are as follows: S1. Weigh 35.1 g of tin tetrachloride pentahydrate (SnCl4·5H2O) and 3.0 g of antimony trichloride (SbCl3), dissolve them in 100 mL of anhydrous ethanol, add 6.2 g of citric acid, adjust the pH of the system to 3.5, and stir the reaction at 60 ℃ for 2 hours to form a sol. Dry the obtained sol at 120 ℃ for 6 hours to obtain a dry gel. Then calcine the dry gel in air at 550 ℃ for 3 hours, cool and pulverize to obtain a light-colored semi-conductive inorganic phase powder with a whiteness of not less than 85% and a median particle size D50 of 1.0 μm.
[0021] S2. Weigh 400 g of environmentally friendly polyester resin, 150 g of quartz powder with a D50 of 8 μm, 30 g of calcium carbonate with a D50 of 0.2 μm and surface coating, 30 g of light-colored semi-conductive inorganic phase, 20 g of environmentally friendly color paste, 5 g of aminosilane coupling agent, 5 g of titanate coupling agent, 10 g of low-migration acrylic leveling agent, 3 g of polyethylene wax powder, and 20 g of curing agent. Add the above raw materials sequentially to a high-speed mixer and mix at 800 r / min for 5 minutes to obtain a premix.
[0022] S3. The premixed material is melt-extruded, with low-temperature segmented temperature zones set: the first segment temperature is 95 ℃, the second segment is 100 ℃, the third segment is 105 ℃, and the die temperature is 100 ℃; the screw speed is controlled at 300 r / min, and the screw shear strength is not greater than 0.8 MPa. The extrudate is cooled and pressed into sheets to obtain sheet material with a thickness of approximately 1 mm.
[0023] S4. The flake material is fed into a high-speed turbine pulverizer for pulverization, controlling the D90 particle size of the final powder to be no greater than 50 μm. After pulverization, it is subjected to cyclone classification and sieving to remove large particles and agglomerates, thereby obtaining the environmentally friendly explosion-proof powder coating for simulating the texture of stone marble.
[0024] Example 2: The stone-touch simulated marble environmentally friendly explosion-proof powder coating comprises the following raw materials in parts by weight: 60 parts resin matrix, 25 parts micron-sized hard phase inorganic filler, 8 parts submicron-sized soft phase inorganic filler, 6 parts light-colored semi-conductive inorganic phase, 5 parts environmentally friendly color paste, 1.2 parts aminosilane coupling agent, 0.8 parts titanate coupling agent, 1.5 parts low-migration acrylic leveling agent, 0.5 parts polyethylene wax powder, and 4 parts curing agent; The preparation steps of the environmentally friendly explosion-proof powder coating for simulating the texture of stone marble are as follows: S1. Weigh 40.5 g SnCl4·5H2O and 4.1 g SbCl3 and dissolve them in 120 mL of anhydrous ethanol. Add 8.0 g citric acid to adjust the pH of the system to 3.0. Stir the reaction in a 70 ℃ water bath for 3 hours. Dry the resulting sol at 120 ℃ for 6 hours. Then calcine the dried gel at 600 ℃ in air for 4 hours. After cooling, grind and sieve to obtain a light-colored semi-conductive inorganic phase powder with a whiteness ≥85% and a median particle size D50 of 3.0 μm.
[0025] S2. Take 600 g of environmentally friendly polyester resin, 250 g of silica powder with a D50 of 25 μm, 80 g of stearic acid-coated talc powder with a D50 of 1.0 μm, 60 g of light-colored semi-conductive inorganic phase, 50 g of environmentally friendly color paste, 12 g of aminosilane coupling agent, 8 g of titanate coupling agent, 15 g of low-migration acrylic leveling agent, 5 g of polyethylene wax powder, and 40 g of curing agent. Mix the above raw materials in a high-speed mixer at 1000 r / min for 8 minutes to obtain a uniformly mixed premix.
[0026] S3. The premix is melt-extruded, with the temperature zones set as follows: first stage 100 ℃, second stage 105 ℃, third stage 110 ℃, and die temperature 105 ℃. The screw speed is set to 400 r / min, and the system shear strength is controlled to be no higher than 0.8 MPa. The extrudate is pressed into sheets by a two-roll cooling device to obtain sheet material with a thickness of approximately 1 mm.
[0027] S4. The flake material is fed into a high-speed turbine pulverizer for pulverization, controlling the final powder's D90 particle size to be no greater than 50 μm. After pulverization, it undergoes cyclone grading and sieving to obtain the environmentally friendly explosion-proof powder coating for simulating the texture of stone marble.
[0028] Example 3: The environmentally friendly explosion-proof powder coating for tactile simulation of marble contains the following raw materials in parts by weight: 50 parts resin matrix, 20 parts micron-sized hard phase inorganic filler, 5.5 parts submicron-sized soft phase inorganic filler, 4.5 parts light-colored semi-conductive inorganic phase, 3.5 parts environmentally friendly color paste, 0.85 parts aminosilane coupling agent, 0.65 parts titanate coupling agent, 1.25 parts low-migration acrylic leveling agent, 0.4 parts polyethylene wax powder, and 3 parts curing agent; The preparation steps of the environmentally friendly explosion-proof powder coating for simulating the texture of stone marble are as follows: S1. Weigh 37.8 g SnCl4·5H2O and 3.5 g SbCl3 and dissolve them in 110 mL of anhydrous ethanol. Add 7.1 g citric acid to adjust the pH to 3.3, and stir the reaction at 65 ℃ for 2.5 hours. Dry the reaction system at 120 ℃ for 5 hours, then calcine it in air at 580 ℃ for 3.5 hours. After cooling, pulverize and sieve to obtain a light-colored semi-conductive inorganic powder with a whiteness ≥85% and a median particle size D50 of 2.0 μm.
[0029] S2. Weigh 500 g of environmentally friendly polyester resin, 200 g of silica powder with a D50 of 16.5 μm, 55 g of coated calcium carbonate with a D50 of 0.6 μm, 45 g of light-colored semi-conductive inorganic phase, 35 g of environmentally friendly color paste, 8.5 g of aminosilane coupling agent, 6.5 g of titanate coupling agent, 12.5 g of low-migration acrylic leveling agent, 4 g of polyethylene wax powder and 30 g of curing agent, add them to a high-speed mixer and stir at 900 r / min for 6 minutes to ensure uniform dispersion of components.
[0030] S3. The premix obtained in step S2 is melt-extruded. The temperature range is set as follows: first stage temperature 97 ℃, second stage 102 ℃, third stage 107 ℃, die temperature 102 ℃, screw speed 350 r / min, and maximum shear strength not exceeding 0.8 MPa. The melt extruded material is cooled and pressed into sheets to obtain sheet material with a thickness of approximately 1 mm.
[0031] S4. The flake material is fed into a high-speed turbine pulverizer for pulverization, controlling the final powder's D90 particle size to be no greater than 50 μm. After pulverization, it undergoes cyclone grading and sieving to obtain the environmentally friendly explosion-proof powder coating for simulating the texture of stone marble.
[0032] Comparative Example 1: No light-colored semiconductive inorganic phase The aforementioned stone-touch simulated marble environmentally friendly explosion-proof powder coating comprises the following raw materials in parts by weight: 50 parts resin matrix, 20 parts micron-sized hard phase inorganic filler, 5.5 parts submicron-sized soft phase inorganic filler, 3.5 parts environmentally friendly color paste, 0.85 parts aminosilane coupling agent, 0.65 parts titanate coupling agent, 1.25 parts low-migration acrylic leveling agent, 0.4 parts polyethylene wax powder, and 3 parts curing agent; The preparation steps of the environmentally friendly explosion-proof powder coating for simulating the texture of stone marble are as follows: S1. Weigh 500 g of environmentally friendly polyester resin, 200 g of silica powder with a D50 of 16.5 μm, 55 g of coated calcium carbonate with a D50 of 0.6 μm, 35 g of environmentally friendly color paste, 8.5 g of aminosilane coupling agent, 6.5 g of titanate coupling agent, 12.5 g of low-migration acrylic leveling agent, 4 g of polyethylene wax powder and 30 g of curing agent, add them to a high-speed mixer and stir at 900 r / min for 6 minutes to obtain a premixed material.
[0033] S2. The premixed material is fed into a twin-screw co-rotating extruder for melt extrusion. The temperatures are set as follows: first stage 97℃, second stage 102℃, third stage 107℃, and die temperature 102℃. The screw speed is set to 350 r / min, and the maximum shear strength is controlled below 0.8 MPa. The extrudate is then pressed into sheets by cooling rollers to form sheets with a thickness of approximately 1 mm.
[0034] S3. The flake material is fed into a high-speed turbine pulverizer for pulverization, controlling the D90 particle size of the final powder to be no greater than 50 μm. After pulverization, it is subjected to cyclone classification and sieving to obtain the environmentally friendly explosion-proof powder coating for simulating the texture of stone marble.
[0035] Comparative Example 2: The mass ratio of micron-sized hard-phase inorganic packing to submicron-sized soft-phase inorganic packing was 10:1. The aforementioned stone-textured simulated marble environmentally friendly explosion-proof powder coating comprises the following raw materials in parts by weight: 50 parts resin matrix, 25 parts micron-sized hard phase inorganic filler, 2.5 parts submicron-sized soft phase inorganic filler, 4.5 parts light-colored semi-conductive inorganic phase, 3.5 parts environmentally friendly color paste, 0.85 parts aminosilane coupling agent, 0.65 parts titanate coupling agent, 1.25 parts low-migration acrylic leveling agent, 0.4 parts polyethylene wax powder, and 3 parts curing agent; The preparation steps of the environmentally friendly explosion-proof powder coating for simulating the texture of stone marble are as follows: S1. A light-colored semiconductive inorganic phase was prepared according to the preparation steps of Example 3.
[0036] S2. Weigh 500 g of environmentally friendly polyester resin, 250 g of silica powder with a D50 of 16.5 μm, 25 g of coated calcium carbonate with a D50 of 0.6 μm, 45 g of light-colored semi-conductive inorganic phase, 35 g of environmentally friendly color paste, 8.5 g of aminosilane coupling agent, 6.5 g of titanate coupling agent, 12.5 g of low-migration acrylic leveling agent, 4 g of polyethylene wax powder and 30 g of curing agent, add them to a high-speed mixer and stir at 900 r / min for 6 minutes to ensure uniform dispersion of components.
[0037] S3. The premix obtained in step S2 is melt-extruded. The temperature range is set as follows: first stage temperature 97 ℃, second stage 102 ℃, third stage 107 ℃, die temperature 102 ℃, screw speed 350 r / min, and maximum shear strength not exceeding 0.8 MPa. The melt extruded material is cooled and pressed into sheets to obtain sheet material with a thickness of approximately 1 mm.
[0038] S4. The flake material is fed into a high-speed turbine pulverizer for pulverization, controlling the final powder's D90 particle size to be no greater than 50 μm. After pulverization, it undergoes cyclone grading and sieving to obtain the environmentally friendly explosion-proof powder coating for simulating the texture of stone marble.
[0039] Performance testing The following performance tests were conducted on the environmentally friendly explosion-proof powder coatings for simulating the texture of marble prepared in Examples 1-3 and Comparative Examples 1-2: Surface roughness Ra test: Referring to GB / T 3505, powder coating samples were sprayed onto the surface of degreased steel plates using the same spraying process. The samples were cured at 180 ℃ for 15 min and then cooled to room temperature to serve as test samples. A three-dimensional white light interferometric profilometer was used to scan the coating surface. Five different regions of each sample surface were measured, and the surface roughness Ra values were recorded and calculated as averages.
[0040] Minimum Ignition Energy Test: After the powder coating samples of the examples and comparative examples were equilibrated under constant temperature and humidity conditions for 24 h, they were tested using a standard dust minimum ignition energy tester. Within the specified dust concentration range, the minimum energy value required to ignite the dust was determined by gradually increasing the discharge energy. The test was repeated 3 times, and the minimum stable ignition energy was taken as the minimum ignition energy (MIE) of the sample.
[0041] Friction coefficient test: Referring to the test method of ASTM D1894, the cured coating sample was cut into the specified size, and the dynamic friction coefficient of the coating surface was tested using a friction coefficient tester under constant load and sliding speed conditions.
[0042] Surface resistance test: Following the test method of GB / T 1410, a surface resistance tester was used to test the surface resistance of the cured environmentally friendly explosion-proof powder coating under standard environmental conditions. A ring electrode measurement method was employed, with three tests performed at different locations on the coating surface, and the average value was taken.
[0043] Color difference ΔE test: Refer to the test method of GB / T 7921, use a spectrophotometer to test the color of the cured coating under D65 light source conditions.
[0044] Table 1 below shows the environmentally friendly explosion-proof powder coatings for simulating the texture of marble prepared in the examples and comparative examples, as well as the performance test results of the coatings. Figure 1 This is a graph showing the relationship between Ra and the coefficient of friction for the examples and comparative examples. Figure 1 It can be seen that as the Ra value of the sample increases, the coefficient of friction also shows a corresponding upward trend, which indicates that the micro-rough structure of the coating directly affects the macroscopic tactile performance.
[0045] Table 1 Performance Test Results
[0046] As shown in Table 1, the dual strategy of "filler particle size distribution control + light-colored semi-conductive inorganic phase conductive network construction" proposed in this invention has successfully achieved multi-dimensional performance synergy of stone tactile feel, decorative consistency and explosion-proof safety.
[0047] In Examples 1-3, the surface roughness Ra were 3.2, 7.6, and 5.1 μm, respectively, all within the comfortable tactile range of simulated stone. This indicates that by optimizing the filler particle size distribution and mass ratio, a stable and controllable microscopic surface structure can be achieved. Among them, Example 3 had the roughness closest to natural stone, achieving consistency between tactile and visual feel. In contrast, Comparative Example 2, due to an unbalanced filler structure, had a Ra as high as 9.3 μm, resulting in excessively high surface roughness and an unbalanced feel.
[0048] Minimum ignition energy (MIE) tests showed that the MIE values of Examples 1-3 were all higher than 50 mJ, with Example 3 reaching 60 mJ, all significantly higher than the 9 mJ of Comparative Example 1. This indicates that the system of the examples has good stability in terms of ignition prevention. The light-colored conductive microchannel constructed in this invention has good charge discharge function and effectively reduces the risk of dust explosion.
[0049] The coefficients of friction for Examples 1–3 were 0.66, 0.82, and 0.74, respectively, indicating that their surface resistance has a certain range of adjustment and shows a regular difference with formula adjustments. Comparative Example 1 had a coefficient of friction of 0.71, which is basically consistent with the range of the Examples, indicating that its frictional feel was not significantly compromised. Comparative Example 2, due to a severe imbalance in particle size distribution leading to a rough surface structure, had a coefficient of friction increasing to 0.95, resulting in a noticeably rougher feel and loss of the stone-like effect.
[0050] Surface resistance test results show that the resistance values of Examples 1 to 3 all fall within 10. 6 ~10 9 The resistance is between Ω, meeting antistatic safety standards, indicating that the designed light-colored semiconducting inorganic phase forms an effective percolation network between powder particles, which facilitates charge dissipation. Example 3, in particular, showed the best performance, with a resistance of 3.8 × 10⁻⁶. 8 Ω ensures safety without compromising aesthetics. Comparative Example 1 shows a resistance as high as 1.2 × 10⁻⁶. 12 Ω represents an insulating state, lacks a conductive mechanism, and poses a serious risk of ignition.
[0051] Color difference tests showed that the ΔE values of Examples 1 to 3 were all below 1.5, making the differences almost imperceptible to the naked eye. In particular, Example 3 had a ΔE value of only 1.1, indicating a highly uniform coating color and a high degree of appearance simulation. In contrast, when Comparative Example 2 was replaced with carbon black conductive agent, the ΔE value rose sharply to 4.6, resulting in a darkened coating surface and noticeable mottling, which severely affected the decorative properties of the stone-like coating.
[0052] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the claimed invention.
Claims
1. A stone-touch simulated marble environmentally friendly explosion-proof powder coating, characterized in that, It contains the following raw materials in parts by weight: 40-60 parts resin matrix, 15-25 parts micron-sized hard phase inorganic filler, 3-8 parts submicron-sized soft phase inorganic filler, 3-6 parts light-colored semi-conductive inorganic phase, 2-5 parts environmentally friendly color paste, 0.5-1.2 parts aminosilane coupling agent, 0.5-0.8 parts titanate coupling agent, 1.0-1.5 parts low-migration acrylic leveling agent, 0.3-0.5 parts polyethylene wax powder, and 2-4 parts curing agent; The mass ratio of the micron-scale hard phase inorganic filler to the submicron-scale soft phase inorganic filler is 4:1 to 6:
1. The median particle size D50 of the micron-sized hard phase inorganic filler is 8–25 μm, the particle size distribution range is D10 ≥ 3 μm, D90 ≤ 40 μm, and the particle size distribution index n is 0.3–0.
5. The submicron-sized soft-phase inorganic filler has a median particle size D50 of 0.2–1.0 μm, a particle size distribution range of D10 ≥ 0.1 μm and D90 ≤ 2 μm, and a particle size distribution index n of 0.6–0.
8. The particle size distribution width (Span) of the composite packing system composed of micron-sized hard-phase inorganic packing and submicron-sized soft-phase inorganic packing is not greater than 2.
5. The light-colored semiconductive inorganic phase is antimony-doped tin dioxide with a whiteness of not less than 85%, a median particle size D50 of 1.0–3.0 μm, and a critical percolation threshold of 4.2% in the powder coating system. The surface roughness Ra of the coating film formed after the powder coating is cured is 3 to 8 μm, and the surface friction coefficient is 0.65 to 0.
85.
2. The environmentally friendly explosion-proof powder coating according to claim 1, characterized in that, The resin matrix is an environmentally friendly polyester resin; the micron-sized hard phase inorganic filler is selected from one or more of quartz powder, talc powder, silica powder, and calcium aluminate; the submicron-sized soft phase inorganic filler is selected from one or more of modified calcium carbonate with surface stearic acid coating, submicron-sized talc powder, submicron-sized kaolin, and submicron-sized wollastonite.
3. The environmentally friendly explosion-proof powder coating according to claim 1, characterized in that: The environmentally friendly color paste is a composite color paste composed of heavy metal-free titanium dioxide and carbon black; the curing agent is triglycidyl isocyanurate.
4. A method for preparing an environmentally friendly explosion-proof powder coating that simulates the feel of natural marble, characterized in that, The environmentally friendly explosion-proof powder coating is the environmentally friendly explosion-proof powder coating according to any one of claims 1 to 3, and includes the following steps: S1. Synthesize a light-colored, semi-conductive inorganic phase; S2. The resin matrix, micron-sized hard phase inorganic filler, submicron-sized soft phase inorganic filler, light-colored semi-conductive inorganic phase, environmentally friendly color paste, aminosilane coupling agent, titanate coupling agent, low-migration acrylic leveling agent, polyethylene wax powder and curing agent are premixed to obtain a premix; S3. The premixed material is melt-extruded, cooled, and pressed into sheets to obtain sheet material; S4. The sheet material is crushed and graded to obtain the stone-touch simulated marble environmentally friendly explosion-proof powder coating.
5. The method for preparing the environmentally friendly explosion-proof powder coating according to claim 4, characterized in that, The synthesis method of the light-colored semiconducting inorganic phase in step S1 is the sol-gel method, which includes the following steps: S101. Dissolve tin tetrachloride pentahydrate and antimony trichloride in anhydrous ethanol, add citric acid, adjust the pH of the system to 3-4, and react under stirring to form a sol. S102. The sol is dried to obtain a dry gel; S103. The dry gel is calcined and pulverized to obtain a light-colored semi-conductive inorganic phase.
6. The method for preparing the environmentally friendly explosion-proof powder coating according to claim 5, characterized in that, In step S101, the molar ratio of tin tetrachloride pentahydrate to antimony trichloride is 100:5 to 100:10; the molar ratio of citric acid to the total amount of metal ions is 1.2:1; the stirring reaction temperature is 60 to 70°C; and the reaction time is 2 to 3 hours.
7. The method for preparing the environmentally friendly explosion-proof powder coating according to claim 4, characterized in that, The premixing in step S2 is carried out using a high-speed mixer with a mixing speed of 800-1000 r / min and a mixing time of 5-8 min; the melt extrusion in step S3 is carried out using a twin-screw extruder with a low-temperature segmented extrusion temperature zone, a screw shear strength of no more than 0.8 MPa, and a screw speed of 300-400 r / min.
Citation Information
Patent Citations
Powder decoration coating and preparation and construction methods thereof
CN106084927A
Hardening liquid and preparation method thereof
CN113308143A